Evaluation of the dose received by ovaries in the treatment of a desmoid tumour presenting in the lower extremity using intensity-modulated radiotherapy tomotherapy - Us, Songul Barlaz; Temelli, Oztun (Cambridge Univ Press, 2017)
Background Desmoid tumour is a rare neoplasm occurring intra- and extra-abdominally. Method In this study, a lower extremity desmoid tumour located close to the ovaries was irradiated with tomotherapy after surgery in a 16-year-old female patient. 30 fractions defined for delivery of 54 Gy were administered to the patient. Result The planning target volume and organs at risk doses were evaluated and the ovary doses were discussed for fertility. Conclusion The patient tolerated the radiotherapy well. During radiotherapy, only grade 1 skin toxicity occurred.
Keywords: desmoid tumour; IMRT; ovary; tomotherapy